OPTIMIZATION OF INDONESIA'S TEA EXPORT STRATEGY TO SOUTH KOREA : AN ANALYSIS OF CONSUMER PREFERENCES AND INTERNATIONAL MARKET CHALLENGES - Setiana, Dani; Hapasari, Ayuningtyas Yuli (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This study aims to explore the optimization of Indonesia's tea export strategy to South Korea by analyzing consumer preferences and the challenges faced in the international market. Utilizing a qualitative research approach, data was collected through in-depth interviews with industry experts, tea producers, and exporters, as well as a review of relevant literature and trade reports. The findings reveal key consumer preferences in South Korea, including flavor profiles, packaging, and perceptions of quality, which significantly influence purchase decisions. Additionally, the study identifies several challenges in the international market, such as regulatory barriers, competition from other tea-exporting countries, and fluctuating demand. These insights are critical for developing targeted strategies that align with market needs and enhance Indonesia's competitive advantage in South Korea. The study concludes with recommendations for stakeholders in the tea industry to improve export performance by addressing consumer demands and overcoming market challenges, thereby optimizing Indonesia’s tea export potential.